Answer:
x=30
Explanation:
Simplifying
6x + 8 = 4(x + 17)
Reorder the terms:
8 + 6x = 4(x + 17)
Reorder the terms:
8 + 6x = 4(17 + x)
8 + 6x = (17 * 4 + x * 4)
8 + 6x = (68 + 4x)
Solving
8 + 6x = 68 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
8 + 6x + -4x = 68 + 4x + -4x
Combine like terms: 6x + -4x = 2x
8 + 2x = 68 + 4x + -4x
Combine like terms: 4x + -4x = 0
8 + 2x = 68 + 0
8 + 2x = 68
Add '-8' to each side of the equation.
8 + -8 + 2x = 68 + -8
Combine like terms: 8 + -8 = 0
0 + 2x = 68 + -8
2x = 68 + -8
Combine like terms: 68 + -8 = 60
2x = 60
Divide each side by '2'.
x = 30
Simplifying
x = 30